Mycobacterium bovis infection in a horse with granulomatous enterocolitis - Sarradell, Javier E.; Alvarez, Julio; Biscia, Mariana; Zumarraga, Martin Jose; Wunschmann, Arno; Armien, Aníbal G.; Perez, Andrés M. (Sage Publications, 2020)
A 2-year-old dappled Percheron horse had a wasting condition that did not respond to antibiotic treatments and ultimately resulted in death. Thickening of the wall of the large colon and enlargement of the mesenteric lymph nodes were observed at postmortem examination, along with the presence of pinpoint whitish foci in the liver. Microscopic examination of affected tissues revealed diffuse chronic granulomatous enterocolitis, granulomatous mesenteric lymphadenitis, and multifocal granulomatous hepatitis. The DNA extracted from paraffin-embedded intestinal and lymph node samples was analyzed using both a polymerase chain reaction (PCR) assay and PCR-restriction endonuclease analysis and demonstrated the presence of Mycobacterium bovis.